Differential antinociceptive effects of intrathecal administration of C‐terminal esterified endomorphin‐2 analogues in mice. (21st February 2014) - Wang, C.L.; Xiang, Q.; Diao, Y.X.; Ren, Y.K.; Gu, N.
Abstract Background We have previously synthesized three esterified endomorphin‐2 (EM‐2) analogues 1–3 by substitution of C‐terminus with methyl, ethyl and tert‐butyl ester, respectively. Interestingly, the increase of EM‐2 in bulkness of the esterified group decreased the μ‐opioid receptor affinity but increased the δ‐affinity. Presently, we extended our studies to investigate the antinociceptive potencies of these esterified analogues given intrathecally in the mouse tail‐flick test. Also, the specific opioid receptor antagonists and antibodies against endogenous opioid peptides were used to determine whether there are any differential mechanisms on the antinociception produced by these analogues. Methods Antinociception was assessed using the 50 °C hot water tail‐flick test. The drugs and antibodies were administered intrathecally. Results The ED50 value of analogue 1 was 1.34 nmol, exhibiting the highest analgesic effect. In contrast, the antinociceptive potency of analogue 2 was about twofold less potent than that of EM‐2. The antinociception induced by analogues 1 and 2 was mediated by the stimulation of μ‐opioid receptor in the spinal cord. However, the analogue 1‐induced antinociception also contained an additional component that was mediated by the release of dynorphin A acting on κ‐opioid receptor, which was similar to its parent EM‐2. Notably, analogue 3 exhibited only slightly lower analgesia relative to EM‐2, which may possibly be due to a direct stimulation of both μ‐ and δ‐opioid receptors. Conclusions Our results demonstrated that EM‐2 and its analogues 1–3 produced differential antinociceptive effects when administered intrathecally. We concluded that C‐terminal amide to esterification conversion changed the antinociceptive potencies and properties of EM‐2.